Review of Ignacio Corona and Alejandro Madrid, eds. 2008. Postnational Musical Identities: Cultural Production, Distribution, and Consumption in a Globalized Scenario. Lanham: Lexington Books - Garland, Shannon (Current Musicology, 2010)
In Postnational Musical Identities, Ignacio Corona and Alejandro Madrid bring together twelve scholars working with (primarily) popular music in (primarily) Mexico and Latin America to consider the relationship between music, identity, and globalization. Assuming that identity is inherent to human subjectivity, the editors analyze the relationship between ethnic and national musical identifications and the globalizing processes that might rearrange, reinscribe, or call into question such correlations. Corona and Madrid layout their frames for thinking about globalization and music (i.e., “The Idea of the Postnational,” “Music Scholarship in Times of Postnationality,” and “The Collapse of Grand Narratives in Popular Music”) in the introductory chapter, “The Postnational Turn in Music Scholarship and Music Marketing.” They rely heavily on cultural studies and postmodernist scholars such as Stuart Hall (1996) and Frederick Jameson (1998), on pop music scholars drawing on these tradition such as Tony Mitchell (1996); on Appadurai’s (1990) basic charter for an anthropology of globalization (his famous “-scapes” framework); and on Hardt and Negri’s (2000) vision of the “postnational,” neoliberal political-economic order.